The Use of Compaction Simulation as a Tool to Aid Successful Tablet Formulation - Sarah Stewart; Inidigo Lily Dean; Mark Lawlor; Simon Lawrence (University of Huddersfield Press, 2022)
Early assessment of compaction properties of both APIs and formulations is an important consideration in early tablet development and can help to de-risk scale up from R&D to production scale. In this work, three model APIs and a tablet formulation were assessed using a compaction simulator. Compaction simulation was shown to be able to differentiate between the compaction properties of APIs and formulations and when combined with additional information on API properties (flowability, solubility) and tablet requirements (size, strength) can guide formulation strategy.